IMPLEMENTASI PEMIKIRAN NURCHOLIS MASJDID BAGI KADER HMI CABANG PALEMBANG - Heryati Heryati; Yusinta Tia Rusdiana (Raudhah - Proud To Be Professional, 2023)
This research is a field research that focuses on examining the implementation of Nurcholis Madjid's thoughts for HMI Palembang Branch using a qualitative descriptive method with an inductive paradigm. These methods and paradigms were chosen on the basis of consideration of the analysis of research problems that require some information from below based on the principles of qualitative research. Historical, sociological, and phenomenological approaches are the choices so that the research objectives can be achieved properly. The research data consisted of primary and secondary data. The results showed that in the Palembang branch of the HMI Cadre, Cak Nur often talked about the need to bring HMI closer to the people, the need to find leaders who really understand Islamic teachings, because HMI can easily fall into secularism, lose direction; and with the failure of the leader will facilitate the occurrence of divisions within the ummah. By maintaining rationalization without westernization, Cak Nur achieved the leadership of HMI which was enthusiastically supported by the mainstream of the reformers, while the traditionalists named him 'Mohammad Natsir Muda'. So that with the influence of Cak Nur's thoughts on rational attitudes in welcoming progress for the Palembang branch HMI cadres, and preventing all possible influences and dangers of liberalism, as well as making efforts to make the Palembang branch HMI more popular through social activities.